Evidence-Based Practice: Applying Research To Nursing Care (Journal of Namibian Studies : History Politics Culture, 2023)
Evidence-based practice (EBP) has become fundamental in modern nursing, guiding clinical decision-making and enhancing patient care outcomes. This paper explores the principles and benefits of EBP in nursing practice. The integration of research evidence, clinical expertise, and patient preferences enables nurses to deliver individualized care that aligns with best practices and improves patient outcomes. This abstract highlights the significance of ongoing education, collaboration, and utilization of technology in implementing EBP. The benefits of EBP include improved patient outcomes, enhanced quality of care, increased patient safety, cost-effective healthcare delivery, and professional development. By embracing EBP principles, nurses can drive practice improvements, promote innovation, and elevate the standard of nursing care.